Algorithms on Sparse Representation - Khalandar Basha, D.; Venkateswarlu, T. (International Journal of Engineering and Technology, 2018)
Representation of signals and images in sparse become more interesting for various applications like restoration, compression and recognition. Many researches carried out in the era of sparse representation. Sparse represents signal or image as a few elements from the dictionary atoms. There are various algorithms proposed by researchers for learning dictionary. This paper discuss some of the terms related to sparse like regularization term, minimization, minimization,  minimizationfollowed by the pursuit algorithms for solving  problem, greedy algorithms and relaxation algorithms. This paper gives algorithmic approaches for the algorithms.